Stuck in the twilight zone? March 2019 municipal elections in Turkey - T. Deniz Erkmen (Stiftung Wissenschaft und Politik (SWP), 2019)
After 16 years of Tayyip Erdoğan in power and with almost total control of the bureaucracy and the mainstream media, it has become hard to imagine a Turkey in which he and his party, the Justice and Development Party (AKP), would not win an election. Yet, after a long nail-biter of an election night, Turkey woke up on April 1 to results indicating a major shift: Defying expectations, Turkish voters had delivered a challenge to the dominance of the governing coalition. While this came as a surprise to some, it points to growing discontent among voters that was able to find expression through institutional means. This was made possible by various parts of the opposition that ran effective alliance strategies and campaigns as well as the election-night process. This accomplishment of the opposition, however, does not necessarily mean an easy shift to a democratic path in Turkey. Much depends on how various actors in the governing coalition respond to this new picture.
Keywords: 320